X.ANDERSENNING “BOLALAR GURUNGI” ERTAGINI PIRLS TOPSHIRIQLARI TUZISH ASOSIDA O‘RGATISH - Hazratqulov, M. (SCIENCE and SOCIETY, 2023)
This article shows the methods of creating PIRLS tasks and analyzing the fairy tale based on H.Andersen's fairy tale. In the analysis of the fairy tale, important recommendations are given on teaching students to think, observe, and react.
Keywords: PIRLS; fairy tale; analysis; creativity; literary education